NEW RECORDS OF SKINKS (SQUAMATA: SCINCIDAE) FROM NAM DONG VALUABLE GYMNOSPERM CONSERVATION AREA, THANH HOA PROVINCE - Khanh Linh, Luong; Quang Vinh, Luu; Quang Truong, Nguyen (Journal of Forestry Science and Technology, 2019)
The Nam Dong Valuable Gymnosperm Conservation Area was recently established in 2014 with 646.95 ha of the core zone and 3,315.53 ha of the buffer zone. The Nam Dong is located in the territory of Quan Son and Quan Hoa districts, Thanh Hoa province. The ecosystem in the protected area is rich and diverse, with the steep and rugged terrain, dense network of rivers and streams. Evergreen limestone karst forests on the karst mountain are the typical habitat in the Conservation Area. The height ranges at elevations from 100 to 900 m above sea level (a.s.l.). However, the family Scincidae has not been studied much, only two species of this family have been recorded so far. Based on a result of our recent field surveys, we collected 11 skink specimens of the family Scincidae. As a result, we recorded six species belonging to four genera of the family Scincidae. Five of them are recorded for the first time from Nam Dong Valuable Gymnosperm Conservation Area, namely: the Bronze Mabuya (Eutropis macularius), Reevesi’s Smooth Skink (Scincella reevesii), Depressed-eared Forest Skink (Sphenomorphus cryptotis), Indian Forest Skink (S. indicus), and Hainan Water Skink (Tropidophorus hainanus). Additional data about natural history data of aforementioned species and an update list of the family Scincidae are provided. The new recorded species in the family Scincidae are found almost in the lowland with the elevation ranges <500 m a.s.l. and 500 - 600 m a.s.l. The presence of T.baviensis needs to be verified by further studies due to morphological similarity between T. hainanus and T. hainanus.